2020
DOI: 10.1093/eurheartj/ehaa377
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes of losartan in patients with Marfan syndrome: follow-up of the multicentre randomized controlled COMPARE trial

Abstract: Aims The COMPARE trial showed a small but significant beneficial effect of 3-year losartan treatment on aortic root dilatation rate in adults with Marfan syndrome (MFS). However, no significant effect was found on clinical endpoints, possibly due to a short follow-up period. The aim of the current study was therefore to investigate the long-term clinical outcomes after losartan treatment. Methods and results In the original C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…Accumulating evidence has demonstrated that losartan and metformin have the potential to delay expansion of the aortic root or abdominal aorta or even prevent this major life-threatening manifestation in patients with MFS or AAA ( 27 , 28 ). Thus, we wondered whether LOXs are involved in the effect of losartan and metformin on the aorta.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that losartan and metformin have the potential to delay expansion of the aortic root or abdominal aorta or even prevent this major life-threatening manifestation in patients with MFS or AAA ( 27 , 28 ). Thus, we wondered whether LOXs are involved in the effect of losartan and metformin on the aorta.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the statistical limitations, the most recent metanalysis of available data showed that AT 1 R antagonism slows the progression of aortic root dilation and is not associated with a statistically significant difference in adverse aortic events [ 366 , 459 ]. Additionally, a recently published long-term follow-up of the multicenter COMPARE trial, which originally reported a small but significant reduction in aortic root dilatation [ 450 ], showed that losartan treatment in MFS patients was associated with a decreased number of adverse aortic events in the treatment group [ 460 ]. Although more studies with sufficient power to confirm this study are both needed and planned, losartan is currently considered an acceptable treatment in combination with β-adrenergic receptor blockers, or when the latter are not tolerated [ 117 , 455 ].…”
Section: Adaptive and Maladaptive Responses In Taa: Implications Fmentioning
confidence: 99%
“…From a clinical perspective, the concept of effective ARB‐mediated attenuation of MFS aortic root growth in the absence of BP lowering may represent a novel but unexpected opportunity to improve patient management. Recent MFS management trials have helped cast doubts about the causal role of BP in aortic root widening, where studies have found no correlation between changes in BP‐lowering and changes in aortic root diameters in patients treated with losartan versus atenolol (Andel et al, 2020; Forteza et al, 2016; Groenink et al, 2013). These doubts have been further materialized in pre‐clinical settings using rodent models of MFS.…”
Section: Discussionmentioning
confidence: 99%